2017
DOI: 10.1007/s10943-017-0399-8
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Tobacco Use: Does Religious Orientation Play a Protective Role?

Abstract: Many studies have established an association between depression and smoking. The main objective of this study was to determine whether religious orientation moderates the relationship between depressive symptoms and tobacco use. This study utilized a cross-sectional data collection strategy to examine the relationship among depressive symptoms, religious orientation, and tobacco use among undergraduate students (N = 349) at a midsize southeastern university. Participants completed a demographic questionnaire, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
2
0
2
Order By: Relevance
“…This is somewhat in contrast with previous findings from studies that established the differentiation of extrinsic religiosity into two separate subscales (personal and social); these studies generally found few significant correlations between the three subscales (Maltby, 2002; Tiliopoulos et al, 2007). However, these studies did not include nonreligious participants, and more recent work involving religious orientation (that included nonreligious participants) has found significant positive correlations between all three orientations (e.g., Osborne, Milojev, & Sibley, 2016; Parenteau, 2018; Parenteau, Waters, Cox, Patterson, & Carr, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is somewhat in contrast with previous findings from studies that established the differentiation of extrinsic religiosity into two separate subscales (personal and social); these studies generally found few significant correlations between the three subscales (Maltby, 2002; Tiliopoulos et al, 2007). However, these studies did not include nonreligious participants, and more recent work involving religious orientation (that included nonreligious participants) has found significant positive correlations between all three orientations (e.g., Osborne, Milojev, & Sibley, 2016; Parenteau, 2018; Parenteau, Waters, Cox, Patterson, & Carr, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…included nonreligious participants) has found significant positive correlations between all three orientations (e.g., Osborne, Milojev, & Sibley, 2016;Parenteau, 2018;Parenteau, Waters, Cox, Patterson, & Carr, 2017).…”
Section: Religious Orientation As a Predictor Of Stigmamentioning
confidence: 98%
“…Ayrıca bu kişiler dini ilkeleri tamamen takip etmeye ve dini içselleştirmeye çalışmaktadırlar. Bireyin dini ihtiyaçları dışındaki diğer ihtiyaçları ne kadar güçlü olursa olsun, daha az önemli görülmekte ve bu ihtiyaçlar mümkün olduğu kadar dini inançlar ve emirlerle uyumlu hale getirilmektedirler (Allport & Ross, 1967: 434;Hichy vd., 2020: 2;Parenteau, 2018Parenteau, : 1213Francis vd., 2016: 2).…”
Section: Dini Yönelimunclassified
“…Bu yönelime sahip kişiler, dini kendi amaçlarına ulaşmak için kullanmaya eğilimlidirler ve gizli güdüler tarafından yönlendirilmektedirler. Bu bireyler, sadece nihai çıkarlarına hizmet ettiği ve diğer ihtiyaçlarına uyum sağladığı sürece dine mensup olmaktadırlar (Allport & Ross, 1967: 434;Hichy vd., 2020: 2;Parenteau, 2018Parenteau, : 1213Francis vd., 2016: 2) hedeflerini gerçekleştirmek için dini araç haline getirmesi olarak ifade edilmektedir (Allport & Ross, 1967: 434;Ercan, 2009: 20;Harlak & Eskin, 2018: 25;Kandemir, 2021: 231).…”
Section: Dini Yönelimunclassified